Dating problems with selected mining lakes and the adjacent groundwater body in Lusatia, Germany - Seebach, Anne Gretje; Rohden, Christoph von; Ilmberger, Johann; Weise, Stephan M.; Knöller, Kay (Isotopes in environmental and health studies, 2010)
This study presents selected results, applying environmental tracers to investigate lake water-groundwater interactions at two study sites located in Lusatia, Germany. The focus of the investigations were two meromictic pit lakes and their adjacent aquifers. In order to follow hydrodynamic processes between lake and groundwater, mixing patterns within the lakes as well as ages of lake and groundwater, water samples of ground- and lake water were collected at three occasions, representing summer and winter conditions in the aquatic systems. The water samples were analysed for stable isotopes (deuterium, oxygen-18) and tritium and sulphurhexafluoride (SF6 concentration). Lake water profiles of conductivity and 18O could validate the permanent stratification pattern of both the lakes. Groundwater data sets showed a heterogeneous local distribution in stable isotope values between rain and lake water. A two-component mixing model had been adopted only from 18O data to determine lake water proportions in the surrounding groundwater wells in order to correct measured tritium and SF6 concentrations in groundwater samples. This procedure had been hampered by upstream-located wells indicating strong 18O enrichment in groundwater samples. However, rough groundwater ages were estimated. For both study sites, Piston flow ages between 12.9 and 27.7 years were calculated. The investigations showed the good agreement between two different environmental dating tools, considering the marginal data sets.
Gesehen am 12.07.2023